Let's start with the function \( f(x) = 4x - 5 \).
Part 1: Calculate \( f(x) \) values
We need to compute \( f(x) \) for different values of \( x \):
-
For \( x = -1 \): \[ f(-1) = 4(-1) - 5 = -4 - 5 = -9 \]
-
For \( x = 0 \): \[ f(0) = 4(0) - 5 = 0 - 5 = -5 \]
-
For \( x = 1 \): \[ f(1) = 4(1) - 5 = 4 - 5 = -1 \]
-
For \( x = 2 \): \[ f(2) = 4(2) - 5 = 8 - 5 = 3 \]
-
For \( x = 3 \): \[ f(3) = 4(3) - 5 = 12 - 5 = 7 \]
Now we can fill in the first table with these results:
| \( x \) | \( f(x) \) | |------------|------------| | -1 | -9 | | 0 | -5 | | 1 | -1 | | 2 | 3 | | 3 | 7 |
Part 2: Find the inverse function \( f^{-1}(x) \)
To find \( f^{-1}(x) \), we need to solve the equation \( y = 4x - 5 \) for \( x \):
-
Replace \( y \) with \( x \): \[ x = 4y - 5 \]
-
Rearranging gives: \[ 4y = x + 5 \] \[ y = \frac{x + 5}{4} \]
Thus, the inverse function is: \[ f^{-1}(x) = \frac{x + 5}{4} \]
Part 3: Calculate \( f^{-1}(x) \) values
Now compute \( f^{-1}(x) \) for the corresponding values of \( x \) in the second table:
-
For \( x = -9 \): \[ f^{-1}(-9) = \frac{-9 + 5}{4} = \frac{-4}{4} = -1 \]
-
For \( x = -5 \): \[ f^{-1}(-5) = \frac{-5 + 5}{4} = \frac{0}{4} = 0 \]
-
For \( x = -1 \): \[ f^{-1}(-1) = \frac{-1 + 5}{4} = \frac{4}{4} = 1 \]
-
For \( x = 3 \): \[ f^{-1}(3) = \frac{3 + 5}{4} = \frac{8}{4} = 2 \]
-
For \( x = 7 \): \[ f^{-1}(7) = \frac{7 + 5}{4} = \frac{12}{4} = 3 \]
Now we can fill in the second table:
| \( x \) | \( f^{-1}(x) \) | |------------|------------------| | -9 | -1 | | -5 | 0 | | -1 | 1 | | 3 | 2 | | 7 | 3 |
With these calculations, we have filled in both tables successfully.